Hubungan Digital Financial Literacy, Facilitating Conditions, Social Influence, Performance Expectancy, Behavioral Intention, Use Behavior terhadap E-Wallet di Indonesia - Tavid, Kevin Akbar; Kurniawati (Universitas Muhammadiyah Palembang, 2024)
The purpose of this study is to investigate the connection between e-wallet adoption in Indonesia and digital financial literacy, facilitation conditions, social influence, performance expectations, behavioral intentions, and user behavior. In the development of computerized monetary innovation, a decent comprehension of the variables that impact conduct e-wallet clients are significant. This study employs a survey method that is sent to people who use e-wallets in different parts of Indonesia. The consequences of relapse strategy and way investigation show that computerized monetary proficiency impacts the conduct aims of e-wallet clients. Likewise, assistance conditions and social impact were additionally demonstrated to contribute essentially to conduct aims. E-wallet execution assumptions likewise assume a significant part in forming client goals. E-wallet users' actual actions are further predicted by strong behavioral intentions. These discoveries give significant bits of knowledge to legislatures, monetary foundations, and e-wallet specialist organizations to foster more powerful showcasing and schooling procedures. Expanding advanced monetary proficiency through instructive missions, further developing access offices, and reinforcing social impact can be vital stages to increment e-wallet reception in Indonesia. Furthermore, e-wallet suppliers can increment client trust by raising execution assumptions and guaranteeing usability of their foundation.